COMMODIFICATION OF CUTURAL HERITAGE AS TOURIST ATTRACTION AT PENATARAN SASIH TEMPLE, PEJENG, GIANYAR - Raka, A.A. Gede Raka; Ardika, I Wayan Ardika; Wirawan, A.A. Bagus Wirawan; Setiawan, I Ketut Setiawan (E-Journal of Cultural Studies; Vol 8 No 2 (2015): Volume 8, Number 2, May 2015, 2015)
Penataran Sasih Temple with the cultural heritage it has is located at Pejeng Village, Gianyar, and is commodified as a tourist attraction. There are three problems which are formulated in the present study. They are (1) what was the cultural heritage which Penataran Sasih Temple, Pejeng, Gianyar, has like; (2) how the process of commodification of the cultural heritage which the Penataran Sasih Temple has took place; (3) what were the impact and meaning of the commodification of the cultural heritage which the Pentaran Sasih Temple has on the people living at Pejeng Village. In general, this present study is intended to identify the commodification of the cultural heritage which the Penataran Sasih Temple has. In particular, this present study is intended to identify the form of the commodification of the cultural heritage, understand the process of the commodification, and explain the impact and meaning of the commodification. The qualitative method was used in the present study. The data were collected through observation, in-depth interview, and library research. The data were analyzed descriptively and qualitatively. It could be inferred that the cultural heritages included (a) the kettledrum “Bulan Pejeng”, the other cultural heritages, and the religious ritual; (b) the commodified cultural heritages were distributed by the government, profit organizations, academicians, and traditional organizations; and (c) the commodified cultural heritages were consumed by the local society, non Balinese society, and international society.
Keywords: commodification, cultural heritage, tourist attraction